The road of bones - Fine, Anne. (London : Corgi Book, 2007)
In Russia, during the reign of communism and one of the many purges that sweep the country, Yuri experiences firsthand the social injustices, labor camp, and starvation.
Kirkus Starred
Publisher's Weekly
School Library Journal
Booklist, June 2008
Horn Book, October 2008
Journal of Adolescent & Adult Literacy, February 2009
Keywords: Communism -- Juvenile fiction; Families -- Soviet Union -- Juvenile fiction; Labor camps -- Juvenile fiction; Communism -- Fiction; Family life -- Soviet Union -- Fiction; Historical fiction; Labor camps -- Fiction; Communism -- Fiction; Family life -- Russia -- Fiction; Historical fiction; Labor camps -- Fiction; Siberia (Russia) -- History -- 20th century -- Juvenile fiction; Soviet Union -- History -- 1925-1953 -- Juvenile fiction; Siberia (Russia) -- History -- 20th century -- Fiction; Soviet Union -- History -- 1925-1953 -- Fiction; Russia -- History -- Fiction; Siberia (Russia) -- History -- Fiction